Facebook groups as transnational counter public sphere for diasporic communities - Mpofu, Phillip; Asak, Moses O.; Salawu, Abiodun (Cogent, 2022)
Mainstream media tend to frame media content from the perspectives of locals and seldom in the interest of diasporic communities. However, the emergence of social media has supported the existence of online diasporic communities. Deploying insights from the concepts of alternative media, digital counter public sphere and hidden transcript, this study explores the use of Facebook groups by Zimbabwean diaspora to form transnational online communities and connect with the homeland. This is a netnographic study of selected Facebook groups of Zimbabweans residing abroad. The study shows that since mainstream media in both home and host countries tend to exclude and marginalise interests of diasporic communities, Facebook has become an alternative counter public sphere for diasporic communities. Due to the affordances of social media, networking sites can be expedient platforms for creating diasporic networks, facilitating information circulation and enabling unrestricted and wide-ranging public debate; however, they can be volatile and susceptible to cybercrime and cyberbullying. The study demonstrates conundrums of online-based communities with regard to issues of trust, legitimacy, accountability and regulation. Research Article; Cultural Studies; 60 Arts & Humanities; 60.2.13 Media Communication; 60.3 Humanities; 60.3.6 Cultural Studies; 60.4 Language & Literature; 60.4.1 Language & Linguistics